Phytochemicals, Antioxidant Profile and GC-MS Analysis of Ethanol Extract of Simarouba glauca Seeds - R, Haleshappa; Patil, Sharangouda J; T, Usha; Murthy, KR Siddalinga (Asian Journal of Biological and Life Sciences, 2020)
Medicinal plants acted as traditional medicine from the ancient time and recognized as scientific medicine in modern days. Simarouba glauca is an Indian traditional medicinal plant commonly called as “Paradise Tree or Lakshmi Taru” used for its various medicinal properties. The current study was carried out to know the phytochemicals, antioxidant profile and Gas Chromatography- Mass Spectroscopy (GC-MS) of ethanol extract of the seed S. glauca. Qualitative analysis showed the presence of flavonoids and carbohydrates, lacked alkaloids, glycosides, steroids, triterpenoids and tannins. The total flavonoid, proanthocyanidin and phenol content were 25.20 ± 0.15mg quercetin equivalent/g extract, 57.08±1.51mg catechin equivalent/g extract and 41.75 ± 2.31mg gallic acid equivalent/g extract respectively. Antioxidants exhibited maximum 2, 2-Diphenyl- 1-picrylhydrazyl (DPPH) scavenging of 70% at 100 μg/mL concentrations with an IC50 value 50.93μg/mL, decolourization potential of 2,2’-azino-bis - (3-ethyl benzthiazoline-6-sulfonic acid (ABTS) was 65% at 203.87μg/mL concentration and ferric reducing antioxidant potential (FRAP) assay exhibited Ascorbic Acid Equivalents (AAE/ml).The relative contents of the fatty acids were calculated with area normalization by GC-MS. Out of the ten fatty acids, four of them were Ethyl oleate (24.20%), Oleic acid (16.13%), 5-Hydroxymethylfurfural (12.69%) and Hexadecanoic acid ethyl ester (12.22%) and other six fatty acids were present less than 11%.
Keywords: Chemical component; Fatty acids; Gc-Ms analysis; Seeds; Simarouba glauca